Managing Disruptions with a Multi-Agent System for Airline Operations Control - Castro, António J. M.; Rocha, Ana Paula (Advances in Practical Applications of Cyber-Physical Multi-Agent Systems: The PAAMS Collection, 2017)
Airline companies face a difficult task in controlling their daily operations, in particular managing irregular operations that result from unexpected disruptions affecting scheduled plans. This demo presents MASDIMA, a Multi-Agent System that manages disruptions in airline operational plans producing intelligent solutions, in the sense that its outcomes are the result of autonomous and collaborative decision making. MASDIMA is able to learn both implicitly, from interactions that happen between their internal agents, and explicitly, from interaction with users.